Mapping the landscape of transformational leadership and competency studies: a bibliometric exploration (1986-2025) - Akther, Naznin; Abdul Hamid, Zabeda; Juhdi, Nurita (RSIS INTERNATIONAL, 2025)
This review paper presents a bibliometric analysis of transformational leadership and competency literature from the year of 1986 to June 2025, analyzing 869 articles from the Scopus indexed databases to identify publication trends, influential authors, countries, contributors, and research themes. Using VOS viewer software, this study examines article titles, co-occurrence keyword analysis, trendy topics, and co-authorship citation networks. The United States, Concordia University, and Sustainability (Switzerland) emerged as leading countries, institutions, and journals, respectively. Keyword analysis revealed themes including digital leadership, digital competence, knowledge sharing, innovation, and sustainability, while highlighting emerging topics such as transformational leadership's impact on teacher knowledge sharing and organizational resilience. Co-authorship analysis revealed the strong international collaboration with the United States, China, and Malaysia as key network nodes. The study emphasizes the dynamic nature of transformational leadership competencies and suggests future research directions in innovative leadership practices, knowledge management integration, and leadership's role in employee innovation and sustainability. These findings provide insights for researchers, practitioners, and policymakers and offer guidance for future research endeavours.